Financing rules of the activity of cultural institutions in the context of economic efficiency - Malgorzata Galecka; Katarzyna Smolny (Institute of Economic Research (IER), 2017)
The aim of this article is the efficiency evaluation of statutory subsidies granted to cultural institutions in the context of subsidizing rules of these institutions. From the economic point of view, the financial analysis of cultural institutions shows economic inefficiency of all institutions. In the majority these are institutions that live on thanks to income from the organizer's subsidies, generating low own revenue in relation to incurred costs. The authors make the argument that subsidized cultural institutions in Poland report heterogeneous financial results despite the fact that their financial management is based on the same financing rules. The authors assume that similar amounts of transfers should provide a comparable range of performed tasks, and thus the access to goods and services supplied. The subject of the study of measuring the economic efficiency of the expenditure of cultural institution are public theatres and music institutions in big cities. The object of the study was limited to cultural institutions whose core business include performing arts.In the paper, while fulfilling the set objective of the study and while verifying the hypothesis graphical method, descriptive statistics, as well as methods of statistical inference have been used. It should be emphasized that despite homogenous principles of granting statutory subsidies, the economic efficiency of individual cultural institutions of culture is diverse. Lack of correlation between the level of financial results, the level of the statuary subsidies and of thetotal costs of a cultural institution leads to conclusion that more factors in this field should be investigated.
Keywords: H7; 330; economic efficiency; public expenditures; cultural institutions; financing rules; subsidies